Exploring the Determinants of Legal Compliance in Small and Medium Enterprises in West Java: Type of Industry, Company Size, Legal Awareness, and Regulatory Burden - Prastiyo Umardani (West Science Law and Human Rights, 2023)
This study explores the determinants of legal compliance in small and medium enterprises (SMEs) in West Java, Indonesia. Specifically, it examines the effects of type of industry, company size, legal awareness, and regulatory burden on legal compliance. Data were collected through a survey of 200 SMEs and analyzed using logistic regression analysis. The results show that type of industry, legal awareness, and regulatory burden significantly influence legal compliance in SMEs. Manufacturing SMEs were found to be more compliant than service SMEs, and SMEs with higher levels of legal awareness were more compliant than those with lower levels. Moreover, SMEs that perceived the regulatory burden to be high were less likely to comply with legal requirements. The study concludes that improving legal awareness and reducing the regulatory burden can be effective strategies to promote legal compliance in SMEs in West Java.